White Negroes : when cornrows were in vogue ... and other thoughts on cultural appropriation - Jackson, Lauren Michele, 1991- (Beacon Press, 2019)
"This book provides a cultural, political, and social survey through the most American of pastimes that continues to thrive today. With narrative, accessible criticism, research, and popular cultural touchstones we can all recognize, I'd like to introduce readers to the black presence that holds up daily life as they know it. It is a crucial account of the people, stories, and culture that create the hilarious, crazy wonder that is life in the 21st century. It is also a wake up call. White Negroes wants to peel open still beating heart of interracial antagonism in this country and expose a form of theft that feels natural only because we are used to it. But we don't have to be. This book documents how this very old tradition shapes our society in the present in the hopes that we can imagine something better. White Negroes will transform what readers think they know about race and culture in the new millennium and open the door to a new present and future unburdened by crimes of the past"--